Hop cultivation vs. weather – an eternal theme - Karel Krofta; Jaroslav Pokorný (Kvasný průmysl, 2023)
The course of weather conditions during the growing season, but also beyond it, decides the economics of hop cultivation every year. Ongoing climate changes manifested by more frequent occurrence of compound hot and dry waves affect hop cultivation not only in the Czech Republic, but in the entire region of Central Europe. The paper evaluates the harvest results (yields, alpha acid content) of four Czech hop varieties in the period 2019–2022 with a focus on the weather diametrically opposed vintages 2021 and 2022 on a specific agricultural farm in the Žatec (Saaz) hop-growing region. While the 2021 vintage was rich in precipitation in the decisive vegetation phase, the 2022 vintage was very dry and hot. The age of the plants significantly influenced the alpha acid content of the varieties Saaz, Sládek and Premiant independently of the vintage. Young growths of the Saaz variety contained at least 60% rel. more alpha acids than older growths (more than 5 years old), while the increase in the Sládek variety was 30–40% rel. and in the Premiant variety 20–25% rel. In the case of the variety Agnus, the age of the plants did not have a demonstrable effect on the content of alpha acids. In 2021 the yields of all varieties were negatively affected by the calamitous occurrence of downy mildew. In 2022, the rainfall deficit was so large that it could not be fully compensated even by the maximum use of drip irrigation. Of the evaluated varieties, the Agnus variety coped best with the different weather conditions of the assessed vintages. This shows that the cultivation of climate resistant varieties is one of the promising but time-consuming ways to face the expected climate changes. Other options include regular renewal of hop growths, consistent regionalization, i.e. planting hop in locations that are suitable for the given variety and efficient use of irrigation systems.